บทบาทนักสังคมสงเคราะห์ในงาน ฟื้นฟูสมรรถภาพผู้ป่วยจิตเวช เข้าสู่การมีงานทำ - จรัสเจริญวิทยา, สมพร (Siriraj Medical Bulletin, 2018)
A role of social worker in mental health rehabilitation for employment that focuses on putting psychiatric patients back into employment includes readiness evaluation, multidisciplinary and social collaboration in order to explore supporting resources for the patient. Supportive counselling and Buddhist psychology are used to create changes within the patients that would enable them to have stable careers and live with others in the society harmoniously.